Revision of the types collection of herbarium of the Institute of botany, National Academy of Sciences, Republic Armenia (ERE), 5. (additions) - Asatrian, M. Ya.; Oganesian, M. E (Армянское ботаническое общество)
The types collection of Herbarium is supplemented by 58 authentic specimens of vascular plants belonging to 15 families, 27 genera, 28 species and 17 taxa of subspecific rank. These specimens includes 1 holotypus, 22 isotypes, 8 syntypes, 4 isolectotypes, 1 isoneotypus, 8 paratypes, 11 authentic specimens. In the collection are included 3 topotypes too. The data of the labels are databased and are already in open access at JACQ database (http: //herbarium.univie.ac.at/database/search.php). All the specimens are scanned and images will be placed in JACQ database and GPI database (http: //plants.jstor.org). The list of these specimens is given. Հերբարիումի տիպային հավաքածուն լրացվել է 58 ավթենտիկ նմուշով, պատկանող 15 ընտանիքի, 27 ցեղի, 28 տեսակի ևենթատեսակային կարգի 17 տաքսոնի: Այս նմուշները պարունակում են 1 հոլոտիպ, 22 իզոտիպ, 8 սինտիպ, 4 իզոլեկտոտիպ, 1 իզոնեոտիպ, 8 պարատիպ, 11 ավթենտիկ նմուշ: Հավաքածուի մեջ ընդգրկվել են նաև 3 տոպոտիպեր: Էտիկետների տվյալները ներմուծվել են JACQ տվյալների բազա ևարդեն ունեն բաց մուտք ( http://herbarium.univie.ac.at/database/ search.php): Բոլոր նմուշները սկանավորվել են և պատկերները կտեղադրվեն JACQ և GPI (http://plants.jstor.org) տվյալների բազաներում: Ներկայացվում է նմուշների ցանկը: Коллекция типов гербария ERE пополнена 58 автентичными образцами, относящимися к 15 семействам, 27 родам, 28 видам и 17 таксонам подвидового ранга. Эти образцы содержат 1 голотип, 22 изотипа, 8 синтипов, 4 изолектотипа, 1 изонеотип, 7 паратипов, 11 автентичных образцов. В коллекцию также включены 3 топотипа. Данные этикеток занесены в базу данных JACQ и уже находятся в открытом доступе (http:// herbarium.univie.ac.at/database/search.php). Все образцы отсканированы и изображения будут размещены в базах данных JACQ и GPI (http://plants. jstor.org). Приводится список образцов.
Keywords: Botany